End-to-End Sample Tracking in the Laboratory Using a Custom Internet of Things Device. (October 2018) - Neil, William; Zipp, Greg; Nemeth, Gregory; Russo, Mark F.; Nirschl, David S.
We describe a custom Internet of Things (IoT) device used for tracking barcoded containers end to end in a high-throughput analysis and purification laboratory. Our IoT device fills an important gap that previously prevented us from fully tracking barcoded sample containers through manual steps in a multistep workflow, such as when samples are "parked" for temporary storage, or when using instrumentation not otherwise equipped with barcode scanners, a common occurrence found with specific centrifugal evaporation instruments. The custom device reads container barcodes and sends a small amount of data to our back-end data systems. Once data have been received and processed, users are alerted to any system responses via aural and visual feedback. Components of the IoT system include a low-cost headless IoT computer, a barcode reader, and a multicolor LED strip. We believe that the model for our device will facilitate simple and rapid deployment of IoT to the broader laboratory community. All source code and device configurations will be released into the public domain and made freely available.